2015
DOI: 10.1039/c4nj02260b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electrical conductivity and optical property of polyaniline-based nanocomposite and its application as an ethanol vapor sensor

Abstract: Polyaniline-Sn(IV)iodophosphate (PANI-SnIP) nanocomposite cation exchanger was synthesized via the sol-gel approach and its AC and DC electrical conductivity, dielectric properties and optical properties were studied. The characterization of the nanocomposite using FT-IR, UV-Vis spectroscopy, SEM and TEM showed the formation of a nanocomposite with improved physicochemical properties. The AC electrical conductivity was found to increase with the increase in applied frequency and concentration of the Sn(IV)iodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…5a shows the UV-vis absorption spectra of {2-(2-pyridyl)benzimidazole}RuCl 3 complex, PANI-Ru, rGO/PANI-Ru and rGO dispersed in DMF solution. For prepared PANI, the characteristic absorption peaks noted at 365 nm and 587 nm are emerges from the excitonic transitions of π and π* polarons-benzoid to quinoide, respectively 55 . The pure Ru complex exhibits a strong absorption band at 334 nm which corresponds to π–π* transition of 2(2-pyridyl)benzimidazole ligand 56 .…”
Section: Resultsmentioning
confidence: 99%
“…5a shows the UV-vis absorption spectra of {2-(2-pyridyl)benzimidazole}RuCl 3 complex, PANI-Ru, rGO/PANI-Ru and rGO dispersed in DMF solution. For prepared PANI, the characteristic absorption peaks noted at 365 nm and 587 nm are emerges from the excitonic transitions of π and π* polarons-benzoid to quinoide, respectively 55 . The pure Ru complex exhibits a strong absorption band at 334 nm which corresponds to π–π* transition of 2(2-pyridyl)benzimidazole ligand 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it can be expected that the electrical conductivity of PANI increases with dispersion process in agreement with the previously reported studies as mentioned earlier. One of the important reasons for the decrease in the energy gap with respect to dispersion process can be due to increase in the density of defect states . Sharma et al reported the width of mobility edge depends on the degree of disorder and defects present in the amorphous structure.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, space charges build up at these macroscopic interfaces under an applied electric field . This occurs in the low frequency range where charge carriers are blocked at the interface of RGO and PAniNTs giving rise to interfacial polarization also known as Maxwell–Wagner–Sillars (MWS) polarization . MWS effect originates from the accumulation of charges at the interfaces within the bulk of the sample forming large dipoles and depends on the conductivity and permittivity of the constituents of the composite material which results in higher values of dielectric constant at low frequencies .…”
Section: Resultsmentioning
confidence: 99%